Stress-Strain State of the Developed Single-Disc Shoe Brake of a Drilling Winch - Janahmadov, А.Kh.; Volchenko, D.A.; Javadov, M.Y.; Fidrovskaya, N.N.; Volchenko, N.A.; Vozniy, A.V. (Herald of Azerbaijan Engineering Academy, 2025)
Theoretical and experimental studies of forced air-nano-liquid cooling of a single-disk shoe brake of a drilling winch have made it possible to establish the following. Improvement of wear-friction properties of friction pairs is achieved due to operation in the temperature range below the permissible ones for friction lining materials and, as a consequence, braking qualities for the lifting shaft of a drilling rig. Application of low-melting metal nanopowders of various modifications diluted with water or acetone for the liquid, which allows to significantly increase the thermal conductivity coefficient of the nanoliquid and thereby improve the efficiency of forced cooling of the friction belts of the brake half-disks. The volumes of nanoliquid in the evaporation zones are much smaller than in the zones of its transport, which intensifies heat exchange in various aggregate states of the nanoliquid due to increased cycles of its circulation. The forced air heat exchange of matte and polished surfaces of the disk by convection and radiation, as well as thermal conductivity, spent on heating the friction belts of the disk, is taken into account, which allows determining a smaller part of the heat removed from their surfaces during braking. Accelerators of the motion of nanofluid in any aggregate state between the zones of evaporation and transport-condensation in their heated state are diffusers, and retarders are the nanostructure of the condensation and transport zone of the disk, which cause a change in the gradients of velocity, pressure and temperature in the layers of nanofluid. With a variable thickness of the friction belt of the disk and the specifics of cooling on the effect of a "heat pipe" using the method of finite element modeling, estimate the stress-strain state of the disk wall.